What tech calls thinking an inquiry into the intellectual bedrock of Silicon Valley - Daub, Adrian 1980- (FSG Originals, Farrar, Straus and Giroux, 2020)
"From FSGO x Logic: a Stanford professor's spirited dismantling of Silicon Valley's intellectual origins."
Keywords: Technologieunternehmen; Informationstechnische Industrie; Silicon Valley; Internet industry / California, Northern; High technology industries / California, Northern; Technology / Social aspects / California, Northern; Information technology / History; Technological innovations / History